The Impact of Diabetic Foot Exercises and Warm Water Foot Soaking Intervention - Cahyandari, Rini; Kalfin; Ibrahim, Riza Andrian (Corespub, 2024)
This study investigates the efficacy of diabetic foot exercises and warm water foot soaking in improving peripheral blood circulation in patients with diabetes mellitus. A paired samples test was conducted to assess the correlation between pre- and post-intervention data. The results revealed a significant correlation (p < 0.05), indicating the effectiveness of the interventions in enhancing peripheral blood circulation. Warm water foot soaking alleviated pain by stimulating endorphin production and dilating blood vessels, while diabetic foot exercises contributed to improved circulation and ulcer prevention. The combined approach holds promise for integrating into comprehensive diabetes care programs to enhance patients' quality of life and prevent complications. Abstract: This study investigates the efficacy of diabetic foot exercises and warm water foot soaking in improving peripheral blood circulation in patients with diabetes mellitus. A paired samples test was conducted to assess the correlation between pre- and post-intervention data. The results revealed a significant correlation (p < 0.05), indicating the effectiveness of the interventions in enhancing peripheral blood circulation. Warm water foot soaking alleviated pain by stimulating endorphin production and dilating blood vessels, while diabetic foot exercises contributed to improved circulation and ulcer prevention. The combined approach holds promise for integrating into comprehensive diabetes care programs to enhance patients' quality of life and prevent complications.